2023
DOI: 10.7554/elife.87756.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aging impairs cold-induced beige adipogenesis and adipocyte metabolic reprogramming

Abstract: The energy-burning capability of beige adipose tissue is a potential therapeutic tool for reducing obesity and metabolic disease, but this capacity is decreased by aging. Here, we evaluate the impact of aging on the profile and activity of adipocyte stem and progenitor cells (ASPCs) and adipocytes during the beiging process. We found that aging increases the expression of Cd9 and other fibrogenic genes in fibroblastic ASPCs and blocks their differentiation into beige adipocytes. Fibroblastic ASPC populations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…Surprisingly, a second adipocyte subpopulation that was almost specific to cold exposed animals (iWAT-ad2) did not express any of the common thermogenic markers, but instead specifically expressed genes involved in lipogenesis (Acss2, Fasn and Acly) (Figure S6G-H). This is in agreement with a recent study showing that expression of lipogenic genes is highly induced in iWAT adipocytes upon cold exposure (Holman et al, 2023). In contrast to iWAT-ad1 and ad2, the abundance of iWAT-ad4 cells decreased by half following cold exposure (Figure S6G).…”
Section: Mprat-ad2 Subtype Is Transcriptionally Different From Iwat A...supporting
confidence: 93%
“…Surprisingly, a second adipocyte subpopulation that was almost specific to cold exposed animals (iWAT-ad2) did not express any of the common thermogenic markers, but instead specifically expressed genes involved in lipogenesis (Acss2, Fasn and Acly) (Figure S6G-H). This is in agreement with a recent study showing that expression of lipogenic genes is highly induced in iWAT adipocytes upon cold exposure (Holman et al, 2023). In contrast to iWAT-ad1 and ad2, the abundance of iWAT-ad4 cells decreased by half following cold exposure (Figure S6G).…”
Section: Mprat-ad2 Subtype Is Transcriptionally Different From Iwat A...supporting
confidence: 93%
“…5 ; Wang et al 2019 ). Seale and colleagues ( Wang et al 2019 ; Holman et al 2023 ) demonstrated that the loss of this metabolite signaling to adipocyte precursors, rather than an intrinsic defect in the adipogenic activity of the cells, may contribute to the age-related decline in the capacity for thermogenic WAT remodeling. Independently, Abe et al (2022) revealed that the proliferation of CD81 + preadipocytes is stimulated by the linoleic acid released from mature adipocytes during the process of lipolysis ( Fig.…”
Section: Adipose Stromal Cells Mediating Adaptative Thermogenic Remod...mentioning
confidence: 99%